Cost Optimization for Logistics Services: A Simulation Approach to Delivery Alternatives - Sihotang, Farida (Spektrum Industri, 2024)
An essential activity in the delivery of goods by logistics service companies is how to deliver goods to consumers according to the agreed time with minimal costs. A case study was conducted on one of the logistics service companies in Bandung, which has an exciting feature: promising goods to consumers within 24 hours. The interesting thing about this company is that it uses the rest of the luggage of travelers traveling to the destination city by plane. In existing conditions, problems often arise, namely, goods do not reach customers according to the agreed time. This causes losses to the company because it must pay a late penalty. Therefore, the author designed several alternatives to meet freight forwarding in less than 24 hours. This study aims to optimize the cost of shipping goods from various alternatives by considering the delivery time of less than 24 hours. This study uses an experimental method with a system model to conduct simulations. Parameters use primary data from the company and secondary data from websites. The author designed two alternatives to shipping goods if no match was found with the traveler. The first alternative is to use air cargo at Bandung Airport. The second alternative is that if it is predicted that the goods will not reach the customer within 24 hours through Bandung Airport, they will be sent to Soekarno Hatta Airport Jakarta using a truck. A match with the traveler at the airport will be sought. The second alternative is also considered if there is no match with the traveler, then the delivery of goods uses air cargo. The simulation results provide a total cost for alternatives 1 and 2 of IDR 69,779,084.40/month and IDR 107,025,296, respectively, for goods that do not meet the delivery of less than 24 hours for alternative 1, namely nine items/month or 1% of the total shipment and alternative 2, namely 19 goods or 2% of the total delivery. The simulation in this study resulted in choosing the first alternative as the best alternative with the lowest cost.